How German vascular surgeons and angiologists judge walking exercise for patients with PAD: Results from a nationwide survey amongst 743 members of two major scientific societies - Rother, Ulrich; Dörr, Gesine; Malyar, Nasser; Müller, Oliver J.; Steinbauer, Markus; Ito, Wulf; Cotta, Livia; Espinola-Klein, Christine; Heckenkamp, Jörg; Behrendt, Christian Alexander (Vasa-Journal of Vascular Diseases, 2023)
Background: To determine the physician s perspective and perception on walking exercise as well as barriers in guideline-directed best medical treatment of patients with lower extremity peripheral arterial disease (PAD). Patients and methods: All members of the German Society for Vascular Surgery and Vascular Medicine and of the German Society for Angiology Society for Vascular Medicine with valid email address were invited to participate in an electronic survey on walking exercise for treatment of intermittent claudication that was developed by the authors. Results: Amongst 3910 invited participants, 743 (19%) provided valid responses (33% females, 84% vascular surgery, 15% angiology). Thereof, 65% were employed by non-university hospitals, 16% by university institutions, and 18% by outpatient facilities. A mean of 14 minutes were spent per patient to counsel and educate, while only 53% responded they had enough time in everyday clinical practice. While 98% were aware of the beneficial impact of structured exercise training (SET) on pain free walking distance and 90% advise their patients to adhere to SET, only 44% provided useful guidance to patients to find local SET programmes and merely 42% knew how to prescribe SET as service that can be reimbursed by medical insurances. Approximately 35% knew a local SET programme and appropriate contact person. Health-related quality of life was assessed in a structured way by only 11%. Forty-seven percent responded that medical insurances should be responsible to implement and maintain SET programmes, while only 4% held hospital physicians responsible to achieve this task. Conclusions: This nationwide survey study amongst vascular specialists illustrates the current insufficient utilisation of SET as an evidence-based therapeutic cornerstone in patients with lower extremity PAD in Germany. The study also identified several barriers and flaws from the physician s perspectives which should be addressed collectively by all health care providers aiming to increase the SET use and eventually its impact on patients with PAD.
CRIS-Team Scopus Importer:2023-07-21
Keywords: best medical treatment; health behaviour; health services research; intermittent claudication; peripheral arterial disease; Walking exercise